Evaluating the Effect of Physician Fellowship Programs on Surgical Outcomes for Coronary Artery Bypass Grafting Procedures. (May 2017) - Delisle, Dennis R.; Nash, David B.
This study examined the relationship between fellowship training of thoracic surgeons and their patient outcomes following a coronary artery bypass graft (CABG) procedure. The study used data obtained from hospital discharges from Florida hospitals from 2006 to 2010 and linked them with the quality of the hospital wherein the physician completed his or her fellowship. Quality rankings were based on the hospital's national ranking among cardiovascular hospitals at the time when the fellowship was completed. A risk-adjusted analysis showed that completing a fellowship in a nationally ranked cardiovascular hospital and a longer time since fellowship and residency completion were associated with lower complication rates for CABG surgeries. This is the first study to incorporate hospital discharge data, external hospital quality rankings, and physician training characteristics to evaluate patient outcomes. Such knowledge could help shape the future direction of health care training and provide an objective, outcomes-based evaluation method for physician training programs.